(untitled) (Journal of Nobel Medical College, 2022)
Background: Acute upper gastrointestinal bleeding is one of the common and life threatening condition presenting in emergency. The aim of the present study was to determine the clinical profile and in-hospital outcomes in these patients admitted at a tertiary care center in Kathmandu, Nepal. Materials and Methods: This is a descriptive, observational study conducted over 9 months (October 2021– July 2022). All consecutive patients aged 16 years and above admitted in the hospital ward with the history of acute bleeding were included in the study after informed consent. Demographic data, clinical, laboratory and endoscopic data were noted during the hospital stay. Statistical analysis was done used SPSS v.24. Results: The mean age of our study population (N = 132) was 46.92 years. Among 132 patients who underwent endoscopy, 43.9% had portal hypertension related bleeding, 41.7% had ulcer related bleeding, 5.3% had malignancies, 3% had corrosive intake. No etiology was found in 3 patients. Hematemesis with melena was the most common mode (53.8%) of presentation to the hospital.Shock was preset in 25% of patients at presentation to the hospital. In-hospital re-bleeding rate and mortality were 12.7% and 9.8% respectively. Conclusion: Portal hypertension related bleeding followed by ulcers related bleeding is the common cause of acute upper gastrointestinal bleeding. In-hospital mortality was 9.8%.